Mildly elevated pulmonary artery systolic pressure on echocardiography: bridging the gap in current guidelines. Issue 10 (October 2021) - Jankowich, Matthew; Maron, Bradley A; Choudhary, Gaurav
Summary: Pulmonary hypertension is associated with increased morbidity and mortality, and growing evidence suggests that even mild elevations in pulmonary artery pressure estimated with echocardiography are linked to increased mortality. In healthy individuals who undergo right heart catheterisation, the average pulmonary artery systolic pressure ranges from 17 mm Hg to 25 mm Hg; on echocardiography, estimated pulmonary artery systolic pressure of more than 30 mm Hg is outside the normal range for most healthy individuals. Increased pulmonary artery systolic pressure (>30 mm Hg) is reported on more than 40% of clinically indicated echocardiograms, often in the presence of metabolic and cardiopulmonary comorbidities, and is associated with a 5-year mortality of 25–40%. However, current guidelines do not sufficiently highlight risk and risk-reduction approaches for the sizable patient population with elevated pulmonary artery pressure who do not have underlying severe pulmonary vascular disease such as pulmonary arterial hypertension. Increased awareness of this frequently reported high-risk echocardiographic finding, and multidisciplinary risk-reduction approaches for patients with metabolic and cardiopulmonary comorbidities and elevated pulmonary artery pressure, are urgently needed.